2014
DOI: 10.1021/cs400906b
|View full text |Cite
|
Sign up to set email alerts
|

Hydroaminomethylation of Styrene Catalyzed by Rhodium Complexes Containing Chiral Diphosphine Ligands and Mechanistic Studies: Why Is There a Lack of Asymmetric Induction?

Abstract: Various chiral diphosphine ligands (P−P) have been introduced in the coordination sphere of neutral or cationic rhodium complexes, and the generated species catalyze efficiently the hydroaminomethylation reaction of styrene with piperidine. The diphospholane ligand family is particularly adapted to this tandem reaction leading to the branched amine with good chemo-and regioselectivity. We analyzed in detail the main reasons why the reaction proceeds with no enantioselectivity. Catalytic and HP-NMR experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…388 Recently, the groups of Urritigoiẗy, Maron, and Kalck investigated the Rh−diphosphine-catalyzed hydrogenation of enamines in the HAM process in more detail and rationalized why this step lacks any enantioselectivity. 389 The mechanism was explored by means of B97D/6-31G(d,p)(SDD) calculations to find that hydride migration from Rh to alkylamine is the ratedetermining step. The lack of enantioselectivity was shown to be a result of equal energies for both (E)-and (Z)-enamine pathways.…”
Section: Hydroformylationmentioning
confidence: 99%
“…388 Recently, the groups of Urritigoiẗy, Maron, and Kalck investigated the Rh−diphosphine-catalyzed hydrogenation of enamines in the HAM process in more detail and rationalized why this step lacks any enantioselectivity. 389 The mechanism was explored by means of B97D/6-31G(d,p)(SDD) calculations to find that hydride migration from Rh to alkylamine is the ratedetermining step. The lack of enantioselectivity was shown to be a result of equal energies for both (E)-and (Z)-enamine pathways.…”
Section: Hydroformylationmentioning
confidence: 99%
“…The hydroaminomethylation of alkenes is a cascade reaction of two consecutive reactions. [74][75][76][77] The alkene substrate first undergoes a hydroformylation reaction 32 to form an aldehyde and then the reductive amination of the resulting aldehyde with an amine produces an N-alkylated amine (Scheme 3). [34][35][36][37]78 Despite the fact that the hydroaminomethylation reaction was originally discovered by Reppe in the early 1950s at BASF using Fe(CO) 5 in nearly stoichiometric amounts, 79,80 intensive research on this topic only started in the past fifteen years.…”
Section: Hydroaminomethylation Of Alkenesmentioning
confidence: 99%
“…Given the plethora of chiral amines among pharmaceutical agents, 1 A study by Kalck using a host of chiral biphosphine ligands revealed no induction of stereochemistry, which was confirmed by computational studies eluding to near isoenergetic pathways for the (E)-and (Z)-enamine hydrogenation, irrespective of the chirality of the ligands. 177 Moreover, the reductive elimination of the final product also proved to be rate limiting. In light of these challenges, an alternative strategy was put forward by Xiao, reasoning that a hydroaminomethylation reaction could be rendered enantioselective if the final enamine can be hydrogenated via a potentially different asymmetric pathway (Scheme 36a).…”
Section: Alkene Aminofunctionalizationmentioning
confidence: 99%